Lecture in the context of modern transformation challenges - Zelenska, L. (Problems of Engineer-Pedagogical Education, 2018)
The article looks into the retrospective analysis of lecture as a form of education in the national high school. The reasons for debate among progressive scientific and educational society of XIX- early XX century on its expediency, advantages and disadvantages due to public demands are determined. The present article reveals theoretical and methodological principles of preparation and conducting of academic lecture as the main form of education in national high school (principles, functions, structure, basic requirements). The attention is concentrated on disadvantages of academic (traditional) lectures in the context of current challenges (globalization, innovations in science and technology, mobility of human resources, realization of the "Program of lifelong learning", etc.). The author's position as to the ways of improving lecture forms of education at the university (combination of leadership of the teacher with students of high activity level through the use of modern innovative (interactive, multimedia, informational) technologies, providing an efficient feedback from students, intensification of pedagogical work, mobilization of thinking, knowledge and skills of students through the introduction of innovative technologies, full implementation of the principle of full educational learning, orientation on the previously mastered by students material of the lecture ) is presented. The most rational and effective ways of transformation the lecture as a form of education due to the modern requirements (problematic lecture, lecture with premeditated errors, "brainstorming", lecture as a press-conference, binary lectures, interactive lectures, etc.) are outlined. The expediency of wide introduction of multimedia and problematic lectures into the high school educational process is proved. Conditions said to be intended to ensure the effectiveness of the introduction of innovations presented are indicated.